Inovasi layanan, citra kesehatan, dan loyalitas pasien: Peran mediasi kepuasan pasien - Wahyuni, Nurul; Suswati, Endang; Rosidi, Rosidi (Journal of Management and Digital Business, 2026)
This research is motivated by the importance of improving the quality of primary healthcare services in building long-term relationships with patients, particularly through service innovation and the formation of a positive image of community health centers. Patient loyalty becomes a crucial aspect as it reflects trust and the continuity of healthcare service utilization. This study aims to examine the effects of service innovation and community health center image on patient loyalty, with patient satisfaction as a mediating variable. The study uses a quantitative, explanatory design. The research population consists of outpatients at the UPTD Community Health Center in Trowulan District, Mojokerto Regency, with a sample of 167 respondents selected using accidental sampling. Data collection was conducted using a Likert-scale questionnaire, and data analysis was performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Research results show that service innovation and the health center's image positively affect patient satisfaction and loyalty. In addition, patient satisfaction acts as a mediating variable, strengthening the relationship between service innovation and the health center's image and patient loyalty.